Section of Court of Abundance (Souvenir Guide Publishers)
On verso: Section of Court of Abundance, showing Tower of Jewels and Arch of Rising Sun in distance. The Fountain of Earth in the foreground. This court is 340 feet square. The surrounding walls are 75 feet high. The Tower is 200 feet high. Designed by Louis C. Mullgardt, of San Francisco, its architecture, though not accredited to any established style, suggests an exquisite combination of Spanish-Gothic.